Strategy For Collection And Distribution Of Zakat Funds In The Etos Id Education Program At LPI Dompet Dhuafa Bogor - Encep Encep; Febriani Mega (Mimbar Agama dan Budaya, 2022)
The development of humanitarian agencies affiliated with educational programs gives its uniqueness to the Dompet Dhuafa Human Development Institute (LPI DD) to innovate in raising funds and empowering educational programs to improve the quality of the nation's children.This study aims the strategy for raising and distributing funds in the Etos ID program at LPI Dompet Dhuafa Bogor. This study uses a qualitative approach with a descriptive method that describes and provides information based on facts obtained from LPI Dompet Dhuafa Bogor.Observation, interviews and documentation carried out data collection techniques carried out in this studyObservation, interviews and documentation carried out data collection techniques carried out in this study. Data analysis in this study uses interactive analysis by collecting, processing, presenting,, and verifying data.The results of research conducted at LPI Dompet Dhuafa Bogor found creative strategies in raising funds, especially during a pandemic,, and channeling funds that provide competitive human resource outcomes needed in 21st-century society; the development of fundraising innovations evidences this, and beneficiary data that has successfully approached 100% financially independent and has excellent achievements and loser opinions regarding his experience while being a beneficiary of Etos ID.